2014
DOI: 10.1038/srep05729
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of chromium and cobalt-related toxicity

Abstract: Occupational and environmental exposure to Co and Cr has been previously linked to a wide array of inflammatory and degenerative conditions and cancer. Recently, significant health concerns have been raised by the high levels of Cr and Co ions and corrosion products released by biomedical implants. Herein, we set to analyze the biological responses associated with Co and Cr toxicity. Histological, ultrastructural, and elemental analysis, performed on Cr and Co exposed patients reveal the presence of corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(173 citation statements)
references
References 58 publications
9
162
2
Order By: Relevance
“…Medical implants are another source of NPs in the human body being released by normal wear. NPs may also enter the body directly as nanomedicines or magnetic resonance imaging (MRI) contrast agents [11][12][13][14]. Given this degree of exposure, it is striking that implications for environmental and human health remain mostly unknown or poorly understood [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Medical implants are another source of NPs in the human body being released by normal wear. NPs may also enter the body directly as nanomedicines or magnetic resonance imaging (MRI) contrast agents [11][12][13][14]. Given this degree of exposure, it is striking that implications for environmental and human health remain mostly unknown or poorly understood [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Co is an essential part of vitamin B12, which is crucial for foliate metabolism. Co harvests reactive radicals and may facilitate free radical production [32] . In our study, we found that serum Co levels were significantly increased in COM patients compared with control subjects.…”
mentioning
confidence: 99%
“…In medicine, inorganic materials are used in implants and in finely divided form (nanoparticles) as nanomedicines or magnetic resonance imaging (MRI) contrast agents. [1][2][3][4] Inorganic engineered nanoparticles (ENMs) are increasingly found in the environment. They are present in batteries, catalysts, chemical coatings, packaging, electronic devices, and cosmetics.…”
Section: Introductionmentioning
confidence: 99%